2020
DOI: 10.1039/c9cp06371d
|View full text |Cite
|
Sign up to set email alerts
|

H-Bonding-mediated binding and charge reorganization of proteins on gold nanoparticles

Abstract: Gold nanoparticles with various functionalities interact with the human serum albumin (HSA) leading to protein structural changes. HSA-nanoparticles bioconjugates display lower toxicity and slower cell uptake rates, compared to nanoparticles in the absence of protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…These polysaccharide coatings have been found to decrease the amount of proteins adsorbed on different types of materials, such as gold NPs (Henriksen‐lacey & Grzelczak, 2015) and carbon surfaces (Zen et al, 2016). Nevertheless, when compared to PEGylated particles, Meeseragandla et al found that glycan‐coated NPs adsorbed a greater amount of HSA molecules (Meesaragandla et al, 2020). These NP‐protein interactions were mostly attributed to the formation of hydrogen bonds, promoted by the presence of hydroxyl groups within the glycan structure, therefore questioning the efficiency of these ligands in preventing corona formation.…”
Section: Protein Corona As a Function Of Nanoparticle Surface Chemistrymentioning
confidence: 99%
“…These polysaccharide coatings have been found to decrease the amount of proteins adsorbed on different types of materials, such as gold NPs (Henriksen‐lacey & Grzelczak, 2015) and carbon surfaces (Zen et al, 2016). Nevertheless, when compared to PEGylated particles, Meeseragandla et al found that glycan‐coated NPs adsorbed a greater amount of HSA molecules (Meesaragandla et al, 2020). These NP‐protein interactions were mostly attributed to the formation of hydrogen bonds, promoted by the presence of hydroxyl groups within the glycan structure, therefore questioning the efficiency of these ligands in preventing corona formation.…”
Section: Protein Corona As a Function Of Nanoparticle Surface Chemistrymentioning
confidence: 99%
“…Both Dex-10 and Cht-AuNPs show similar d H , even though the core size was different as shown in TEM images. This could be due to the multilayer adsorption of polymers on AuNPs surface 27,28 . Among all the biopolymer-coated AuNPs, a large increment in the d H was observed for the Dxt-AuNPs, which is due to the multilayer linear adsorption of Dxt molecules.…”
Section: Synthesis and Characterization Of Biopolymer-coated Aunps Bmentioning
confidence: 99%
“…Instead, these nano–bio interactions might be driven by other mechanisms, such as hydrogen bonding and hydrophobic interaction, as reported in previous works. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%